Persepsi Mahasiswa Mengenai Dampak Undang-Undang Kesehatan No. 17 Tahun 2023 Terhadap Profesi Tenaga Vokasi Farmasi - Rani Tiara Desty; Dwi Subarti; Dessy Ratna Sari (Universitas Ivet, 2026)
Health Law No. 17 of 2023 brought significant changes to the health system in Indonesia, particularly regarding the health care profession. The purpose of this study to determine the perceptions of pharmacy students regarding the impact of Health Law No. 17 of 2023 on the health care profession. This type of research was quantitative descriptive research with a cross-sectional approach. The population in this study were all Pharmacy Diploma III Study Program Students, Class of 2024. The sample taken in this study was a total sampling of 148 students. The variable studied was students perceptions regarding the impact of Health Law No. 17 of 2023 on the health care profession. The instrument used was a questionnaire with a Google form. The results showed that the majority of respondents were female (91.1%). More than half (55.5%) of respondents were 19 years old. More than half of the students (98.6%) have heard/read Law No. 17 of 2023. Half of the students (50%) have a good perception of Law No. 17 of 2023. Education for students regarding Law No. 17 of 2023 is necessary, so that they can understand, have good readiness and motivation for the dynamics of the profession in the future.